Novel electrosynthesis of CdS/FeS nanocomposite-modified poly(o-phenylenediamine) with views to their use as a biosensor for Escherichia coli. - Hernández, Loreto; Martín-Jiménez, Francisco de Paula; Berrios, Eduardo; Riveros, Gonzalo; González, Darío M; González, Ernesto; Lizama, Susy; Hernández, Franco (Elsevier, 2020)
This article proposes a new electrochemical sensor for Escherichia coli (E. Coli) com- posed of poly(o-phenylenediamine) (PoPD) and CdS/FeS nanocomposites (PoPD|CdS/FeS). The preparation of the modified electrodes used for this purpose and their subsequent use as a sensor comprise a simple, fast and reproducible technique. The characterization of the CdS/FeS nanocomposites and their subsequent inclusion on PoPD was performed by X-ray diffraction (XRD), Raman, field emission scanning electron microscopy (FESEM), high-resolution transmission electron microscopy (HR-TEM) and computational methods; For the nanocomposites an average size of 100 nm was obtained after applying a reduction potential for 5 s over the polymeric matrix. The electrochemical characterizations confirmed that the inclusion of the nanocomposites improved the amperometric response, allowing the developed material to be used as an electrochemical sensor for E. Coli. The figures obtained gave the linear equation j = -6.89 x 10-14 x CFU + 5.64 x 10-5, with an R2 of 0.995, for 10 replicates. Furthermore, the limit of detection (LOD) was 6.1 x 105 CFU/mL, and the limit of quantification (LOQ) was 6.1 x 106 L.
Keywords: Enfermedades de origen alimentario; Sensores electroquímicos; Polymers; Poly(o-phenylenediamine); Nanocomposites; CdS; FeS; Escherichia coli